Various unusual presentation of acute appendicitis in adult. A case series - Barman, Amalesh; Panja, Madhusudan; Samanta , Riddhisundar; Ranajit Bari (Asian Journal of Medical Sciences, 2023)
Acute appendicitis is common abdominal condition in our day to day surgical practice. Classical features include periumbilical pain that migrates to the right iliac fossa, anorexia, fever, and tenderness and guarding in the right iliac fossa. However, in our present study, three atypical presentation of acute appendicitis is demonstrated in clinical practice. These three cases do not have classical features of murphy’s triad, that is, nausea, vomiting, fever, and cardinal sign of positive Mcburney’s tenderness. Our three atypical cases are: (1) A 38 year old obese male patient who presented with features of umbilical inflammation with serous discharge due to presence of acute inflamed appendix in pre-existing small umbilical hernial sac. (2) A 49-year-old male medicine seller presented right sided scrotal pain with same sided inguino-scrotal swelling for short duration due to presence of inflamed swollen tip of appendix at bottom of right hemi-scrotum in pre-existing inguinal hernia. (3) A 81-years-male gentleman presented with anorexia, weakness, abdominal fullness, and bilateral pedal edema. He did not have pain abdomen, fever, and right iliac fossa tenderness. Imaging modalities confirmed the acute appendicitis in three cases. Diagnosis of appendicitis in absence of typical features is to be made from pre-occupied knowledge and with help of imaging studies.